Deletion of murine slc29a4 modifies vascular responses to adenosine and 5‐hydroxytryptamine in a sexually dimorphic manner. Issue 5 (13th March 2020) - Wei, Ran; Gust, Stephen L.; Tandio, David; Maheux, Alexia; Nguyen, Khanh H.; Wang, Joanne; Bourque, Stephane; Plane, Frances; Hammond, James R.
Abstract: Equilibrative nucleoside transporter 4 (ENT4), encoded by SLC29A4, mediates the flux of both 5‐hydroxytryptamine (5‐HT) and adenosine across cell membranes. We hypothesized that loss of ENT4 function in mice would modify the effects of these established regulators of vascular function. Male and female wild‐type (WT) and slc29a4 ‐null (ENT4‐KO) mice were compared with respect to their hemodynamics and mesenteric vascular function. Male ENT4‐KO mice had a complete loss of myogenic tone in their mesenteric resistance arteries. This was accompanied by a decrease in blood flow in the superior mesenteric artery in the male ENT4‐KO mice, and a reduced responsiveness to 5‐HT. In contrast, endothelium‐dependent relaxations of mesenteric arteries from female ENT4‐KO mice were more sensitive to Ca 2+ ‐activated K + (KCa ) channel blockade than WT mice. Female ENT4‐KO mice also demonstrated an enhanced vasodilatory response to adenosine in vivo that was not seen in males. Ketanserin (5‐HT2A inhibitor) and GR55562 (5‐HT1B/1D inhibitor) decreased 5‐HT‐induced tone, but only ketanserin inhibited the relaxant effect of 5‐HT in mesenteric arteries. 5‐HT‐evoked increases in tone were elevated in arteries from ENT4‐KO mice upon block of endothelial relaxant pathways, with arteries from female ENT4‐KO mice showing the greatest increase. Adenosine A2b receptor expression was decreased, while other adenosine transporter subtypes, as well as adenosine deaminase and adenosine kinase were increased in mesenteric arteries from male, but not female, ENT4‐KO mice. These findings indicate that deletion of slc29a4 leads to sex‐specific changes in vascular function with significant consequences for regulation of blood flow and pressure by adenosine and 5‐HT. Abstract : Loss of the adenosine/5‐HT transporter ENT4 (encoded by slc29a4) leads to sex‐specific changes in vascular regulation in the ENT4‐null mouse. Male mice have a complete loss of myogenic tone in their mesenteric arteries, while mesenteric arteries from female mice exhibit a change in the relative contributions of nitric oxide and KCa channels to vascular regulation. The vascular effects of both adenosine and 5‐HT are enhanced in slc29a4‐null mice. These data indicate that ENT4 plays an important role in the modulation of adenosine and 5‐HT activity in normal vascular function.